Nitrogen dioxide sensing based on multiple-morphology cuprous oxide mixed structures anchored on reduced graphene oxide nanosheets at room temperature. (27th August 2019) - Zhu, Xiangyi; Zhou, Yong; Guo, Yongcai; Ren, Hao; Gao, Chao
Abstract: Sensitive detection of trace nitrogen dioxide (NO2 ) gas at room temperature is of urgent necessity in the fields of healthcare and environment monitoring. To achieve this goal, we report on a porous composite film featuring reduced graphene oxide (rGO) nanosheets as the template platform of nanostructured cuprous oxide (Cu2 O) nanowires and nanoparticles via a hydrothermal method. The sensor performance was investigated in terms of sensing response, optimal operation temperature, repeatability, long-term stability, selectivity and humidity effect on NO2 sensing. The sensor response achieved 0.66 towards 50 ppb NO2 gas with a full recovery at room temperature (25 °C ± 2 °C), which was among the best cases of Cu2 O-related NO2 detection concerning sensor response and operation temperature. Moreover, a modest repeatability, stability, selectivity as well as a negligible humidity effect on NO2 sensing were exhibited. A mass of interspaces existing within nanostructured composites as well as the synergistic effect between rGO and Cu2 O materials endowed the sensing layer with favorable gas accessibility and sufficient gas–solid interaction. Simultaneously, highly conductive rGO nanosheets facilitated an effective electron transfer and collection. In brief, the as-prepared rGO/Cu2 O sensors showed a competitive room temperature detection capability for ppb-level NO2 gas, providing a vast potential in the future applications such as the real-time monitoring of ultralow emission.